Self‐management programmes in temporomandibular disorders: results from an international Delphi process. (1st November 2016) - Durham, J.; Al‐Baghdadi, M.; Baad‐Hansen, L.; Breckons, M.; Goulet, J. P.; Lobbezoo, F.; List, T.; Michelotti, A.; Nixdorf, D. R.; Peck, C. C.; Raphael, K.; Schiffman, E.; et al.
Summary: Self‐management (SM) programmes are commonly used for initial treatment of patients with temporomandibular disorders (TMD). The programmes described in the literature, however, vary widely with no consistency in terminology used, components of care or their definitions. The aims of this study were therefore to construct an operationalised definition of self‐management appropriate for the treatment of patients with TMD, identify the components of that self‐management currently being used and create sufficiently clear and non‐overlapping standardised definitions for each of those components. A four‐round Delphi process with eleven international experts in the field of TMD was conducted to achieve these aims. In the first round, the participants agreed upon six principal concepts of self‐management. In the remaining three rounds,  consensus was achieved upon the definition and the six components of self‐management. The main components identified and agreed upon by the participants to constitute the core of a SM programme for TMD were as follows: education; jaw exercises; massage; thermal therapy; dietary advice and nutrition; and parafunctional behaviour identification, monitoring and avoidance. This Delphi process has established the principal concepts of self‐management, and a standardised definition has been agreed with the following components for use in clinical practice: education; self‐exercise; self‐massage; thermal therapy; dietary advice and nutrition; and parafunctional behaviour identification, monitoring and avoidance. The consensus‐derived concepts, definitions and components of SM offer a starting point for further research to advance the evidence base for, and clinical utility of, TMD SM.